The future of teaching and learning: students' attitudes toward the use of artificial intelligence - Gheție, Romina; Rad, Dana; Cuc, Lavinia Denisia; Rădulescu, Dan (Technium Business and Management, 2025)
This study explores the attitudes of university students from Western Romania regarding the use of artificial intelligence (AI) in education. A total of 600 valid responses were collected from students enrolled in various specializations and forms of study. The research aims to understand students' perspectives on the integration of AI in educational settings, examining their views on the current and future roles of AI in shaping the teaching and learning experience. The questionnaire aimed to capture the opinions of students concerning the potential benefits and challenges of AI, as well as its impact on their academic development and future career prospects. The findings provide valuable insights into how students perceive the evolution of AI technologies and their potential to transform educational practices in Romania. These results may inform educators and policymakers on how to better integrate AI tools into the academic environment, aligning with student expectations and the future demands of the workforce.